2002
DOI: 10.4269/ajtmh.2002.66.431
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Rickettsia typhi and the potential for murine typhus in Jayapura, Irian Jaya, Indonesia.

Abstract: Abstract. Murine typhus (etiologic agent: Rickettsia typhi) is endemic to Indonesia, especially on the highly populated island of Java. A survey of rodents from Irian Jaya, the eastern-most province of Indonesia, indicated striking geographic variation in risk factors associated with murine typhus. Murid rodents (n ‫ס‬ 112) collected from two villages in the Arso district of northeastern Irian Jaya, were found to be free of ectoparasites normally associated with transmission of R. typhi (i.e., Xenopsylla cheop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…However, other rodent species and cats have also been implicated as reservoirs and cats fleas can also transmit the infection. 12,32,33,50,51 Overcrowding, poor public health and sanitation measures provide ideal conditions for transmission of murine typhus. In addition, clearing of land for urban development and construction enable rodent populations to increase and expose humans to the zoonotic life cycle, thus leading to increasing seroprevalence observed in some of the rapidly developing countries, such as Malaysia.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…However, other rodent species and cats have also been implicated as reservoirs and cats fleas can also transmit the infection. 12,32,33,50,51 Overcrowding, poor public health and sanitation measures provide ideal conditions for transmission of murine typhus. In addition, clearing of land for urban development and construction enable rodent populations to increase and expose humans to the zoonotic life cycle, thus leading to increasing seroprevalence observed in some of the rapidly developing countries, such as Malaysia.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…[26][27][28][29] Socioeconomically, agricultural, plantation, or forest workers in Thailand, Malaysia, and Indonesia were frequently affected by scrub typhus and SFGR infections. 21 [32][33][34][35][36][37][38] Rodents were found to be important reservoirs for SFGR and murine typhus; high seropositive rates (up to 39.1% for SFGR) were observed in some parts of rural Indonesia. 32,33 Infection of rat flea Xenopsylla cheopis with R. felis has also been found in Indonesia, which increases the possibility of human infections with R. felis in the region, although no clinical case has been reported to date.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Murine typhus (also known as endemic typhus and ßeaborne typhus), caused by Rickettsia typhi, is found worldwide. Indonesia has one of the highest prevalence levels of antibodies to R. typhi among people in the world (Richards et al 2002). Studies in Java found that people living in urban areas had a higher prevalence of antibodies to R. typhi than less urban areas with lower concentrations of people (Richards et al 2002).…”
mentioning
confidence: 99%
“…Indonesia has one of the highest prevalence levels of antibodies to R. typhi among people in the world (Richards et al 2002). Studies in Java found that people living in urban areas had a higher prevalence of antibodies to R. typhi than less urban areas with lower concentrations of people (Richards et al 2002). Flea-borne spotted fever (cat ßea typhus) caused by Rickettsia felis has been identiÞed in Ctenocephalides felis found in North America, Europe, Africa, Asia, Australia, and New Zealand and in X. cheopis in Java, Indonesia (Jiang et al 2006).…”
mentioning
confidence: 99%